Pengaruh Digital Banking terhadap Kepuasan Nasabah pada Era Transformasi Digital - Achmarul Fajar; Aprial Trihandy; Syindina Anansyah; Siti Aisyah legenda (Jurnal Riset Multidisiplin Edukasi, 2026)
Digital transformation has driven the banking industry to develop technology-based services, one of which is digital banking. The implementation of digital banking is expected to improve service quality and customer satisfaction amid increasingly dynamic changes in consumer behavior and needs. This study aims to analyze the effect of digital banking on customer satisfaction in the era of digital transformation. The research method employed is a literature review with a qualitative approach, using secondary data obtained from various relevant national and international journal articles related to digital banking and customer satisfaction. Data analysis techniques were conducted through the identification, selection, and synthesis of findings from previous studies. The results of the review indicate that digital banking generally has a positive effect on customer satisfaction, as reflected in ease of use, transaction speed, system reliability, and enhanced customer experience. However, several challenges, such as data security issues, system disruptions, and differences in levels of digital literacy, remain factors that may influence customer satisfaction. This study concludes that the success of digital banking in improving customer satisfaction largely depends on the quality of digital services, system security, and the bank’s ability to adapt its services to the needs and characteristics of its customers. The findings of this study are expected to serve as a reference for the banking industry and future research related to the development of digital banking services.